2021
DOI: 10.3390/ijerph182010725
|View full text |Cite
|
Sign up to set email alerts
|

Government Health Expenditure and Public Health Outcomes: A Comparative Study among EU Developing Countries

Abstract: The aim of this paper was to empirically analyze the relationship between public health expenditure and health outcomes among EU developing countries. Using regression analysis and factor analysis, we documented that public health expenditure and health outcomes are in a long-run equilibrium relationship and the status of health expenditure can improve life expectancy and reduce infant mortality. Secondarily, we studied how the status of good governance, health care system performance, and socioeconomic vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 56 publications
(57 reference statements)
6
36
0
Order By: Relevance
“…In the same vein, life expectancy and health indicate a U-shape relationship. That is, initial increase in health expenditures causes a decline in life expectancy but additional increase in health expenditures results in improving life expectancy Again, this finding aligns with the empirical literature [22].…”
Section: Pre-estimation Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the same vein, life expectancy and health indicate a U-shape relationship. That is, initial increase in health expenditures causes a decline in life expectancy but additional increase in health expenditures results in improving life expectancy Again, this finding aligns with the empirical literature [22].…”
Section: Pre-estimation Resultssupporting
confidence: 88%
“…The nexus between health expenditures and health outcomes is well established in the literature for both developing and developed countries. For example, Onofrei, Vatamanu, Vintila and Cigu [22], analysed the relationship between public health expenditure and health outcomes among European Union developing countries via regression and factor analysis. The study concluded that public health expenditure can improve life expectancy at birth and infant mortality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the effect of government health, education and infrastructure expenditure on the HDI, Safitri (2016) employed panel data from 23 districts over the period 2008-2014 and found only the spending on health has a significant impact on the HDI improvement. Most recent studies have been conducted by Ibukun (2021) and Onofrei et al (2021) on the role of governance in the effectiveness of health expenditure to achieve different health outcomes such as mortality rate (MR) or life expectancy at birth, respectively. Although their findings are not directly linked to human development, they found a positive relationship between health expenditure and life expectancy and a negative relationship with the MR.…”
Section: Good Governance and Human Developmentmentioning
confidence: 99%
“…The interaction of CO 2 and health expenditure also stipulates a negative impact on health. In literature, several studies have shown a positive and significant effect of state expenditure in the health sector on human health status (Boachie and Ramu, 2016;Farag et al, 2013;Onofrei et al, 2021;Shuaibu and Timothy, 2016).…”
Section: Introductionmentioning
confidence: 99%